Effect of Hubbard U-corrections on the electronic and magnetic properties of 2D materials: a high-throughput study - Sahar Pakdel; Thomas Olsen; Kristian S. Thygesen (npj Computational Materials)
Abstract We conduct a systematic investigation of the role of Hubbard U corrections in electronic structure calculations of two-dimensional (2D) materials containing 3d transition metals. Specifically, we use density functional theory (DFT) with the PBE and PBE+U approximations to calculate the crystal structure, band gaps, and magnetic parameters of 638 monolayers. Based on a comprehensive comparison to experiments we first establish that the inclusion of the U correction worsens the accuracy for the lattice constants. Consequently, PBE structures are used for subsequent property evaluations. The band gaps show a significant dependence on U. In particular, for 134 (21%) of the materials the U parameter induces a metal-to-insulator transition. For the magnetic materials we calculate the magnetic moment, magnetic exchange coupling, and magnetic anisotropy parameters. In contrast to the band gaps, the size of the magnetic moments shows only weak dependence on U. Both the exchange energies and magnetic anisotropy parameters are systematically reduced by the U correction. On this basis we conclude that the Hubbard U correction will lead to lower predicted Curie temperatures in 2D materials. All the calculated properties are available in the Computational 2D Materials Database (C2DB).